13 Multimorbidity and physical activity recommendations in european older adults. (20th December 2017) - Sarmento, H; Peralta, M; Marques, A
Abstract : Physical activity (PA) has been associated with decreased risks of several chronic conditions and mortality. Although the association between multimorbidity (co-occurrence of more than one chronic disease in one person) and PA has been investigated, recent studies of this topic yield dissenting results and few studies examine attaining PA recommendations in the older adult population. Thus, the aim of this study was to examine the associations between multimorbidity and attaining PA recommendations in the European older adult population. Participants were 8195 older adults (Mage=74±7 years; 3847 men) who responded to European Social Survey round 7, in 2014. Information was collected through a questionnaire, filled-in during an hour-long face-to-face interview. Meeting the PA recommendations was accessed using the European Union Physical Activity Guidelines (≥30 min of at least moderate physical activity, ≥5 times per week). Descriptive statistics were calculated and the Chi-square and Fisher's exact test were used to verify gender differences. The association between attaining PA recommendations and multimorbidity was assessed using logistic regression models. Overall, 41% of the older adults had multimorbidity and only 32.0% attained the PA recommendations. Furthermore, the prevalence of multimorbidity was higher among women than it was for men (43% vs 39%). For both men and women, attaining the PA recommendations was associated with lower odds of having multimorbidity (men, OR: 0.69, CI: 0.59–0.80, p<0.001; women, OR: 0.68, CI: 0.59–0.79, p<0.001). Attaining PA recommendations has a positive effect on health, decreasing the risk for multimorbidity, however many European older adults are not active enough. These findings should raise public health concern regarding the PA levels of the European older adult population and its impact on health. Continuous action for promoting PA is advised.